The Network Concept of Strategic Management and Its Limitations = Sieciowa koncepcja zarządzania strategicznego i jej ograniczenia - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
The purpose of the article is to contribute to the discussion on the network concept of strategic management and the limitations thereof. The article opens with a presentation of the origin of the concept of network organizations, which further on allows the author to discuss the concept of networks in strategic management, pinpoint its limitations and assess the validity of the assumption that a new paradigm of the strategic management theory is emerging.
Keywords: The concept of network organization; Strategic management; Koncepcja organizacji sieciowej; Zarządzanie strategiczne